Multiple Criteria Decision-Making Methods : Applications for Managerial Discretion - Anand, Adarsh; Agarwal, Mohini; Aggrawal, Deepti (Walter de Gruyter GmbH, 2022)
This book provides application of multi criteria decision making techniques for managerial discretion. With this book, a concerted platform has been provided for several peers and other management organizations to understand and implement these tools and deal with the practical problems in a better way so as to provide more robust managerial decision making.
Keywords: Decision making -- Mathematical models.; elektronické knihy; electronic books